1998
DOI: 10.1007/s11745-998-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatty acid monomers from dietary heated fats affect rat liver enzyme activity

Abstract: This study was conducted to investigate the effects of dietary cyclic fatty acid monomers (CFAM), contained in heated fat from a commercial deep-fat frying operation, on rat liver enzyme activity. A partially hydrogenated soybean oil (PHSBO) used 7 d (7-DH) for frying foodstuffs, or 0.15% methylated CFAM diets was fed to male weanling rats in comparison to a control group fed a nonheated PHSBO (NH) diet in a 10-wk experiment. All diets were isocaloric with 15% fat. Animals fed either CFAM or 7-DH diets showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Although there exists some evidence that dietary CFAM have a negative impact on the development of fatty liver (Lamboni et al, 1998), evidence on the underlying mechanisms leading up to fat accumulation in the liver is still limited. To the best of our knowledge, this is the first study to assess the impact of CFAM combined with two different dietary oils on markers of hepatic steatosis in relative low‐fat diet fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although there exists some evidence that dietary CFAM have a negative impact on the development of fatty liver (Lamboni et al, 1998), evidence on the underlying mechanisms leading up to fat accumulation in the liver is still limited. To the best of our knowledge, this is the first study to assess the impact of CFAM combined with two different dietary oils on markers of hepatic steatosis in relative low‐fat diet fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that dietary oxidized oils reduce triglyceride concentrations in plasma and liver. Recent studies demonstrated that the activities of glucose-6-phosphate dehydrogenase (8) and other enzymes involved in the synthesis of fatty acids in the liver (13) are reduced by dietary lipid peroxidation products. Thus, reduced concentrations of triglycerides in plasma and liver might be caused by a reduced rate of lipogenesis.…”
Section: Tablementioning
confidence: 99%
“…On the other hand, this study as well as others (6,7,11,34) reported increased liver weights in animals fed oxidized oils. It has been shown that the enlargement of liver is largely due to a proliferation of endoplasmic reticulum, which is indicated by the induction of microsomal detoxifying enzymes (8,10). This also might explain the significant increase in phospholipid content in the liver and the increased ratio between phospholipids and cholesterol.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these reactions lead to the formation of cyclic fatty acid monomers (CFAM), mainly from 18:3n-3 and 18:2n-6 (2)(3)(4). When fed to rats as a purified fraction, these CFAM are incorporated into cellular lipids (4), and those formed from linolenic acid (Ln) have been associated with several adverse effects such as poor growth and high mortality after birth (4), alteration of electrophysiological parameters as well as resistance to reoxygenation after hypoxia of heart cells in culture (5), and modification of some enzymatic activity in liver (6,7), intestine (8), or cultured endothelial cells (9).…”
mentioning
confidence: 99%